Clinicopathological Factors associated to Her-2 Status in a Hospital-based Sample of Breast Cancer Patients in Puerto Rico - Ortiz, Ana P.; Frías, Orquídea; González-Keelan, Carmen; Suárez, Erick; Capó, David; Pérez, Javier; Cabanillas, Fernando; Mora, Edna (Puerto Rico Health Sciences Journal, 2010)
Breast cancer is the most common female malignancy in Puerto Rico. Cases with human epidermal growth factor receptor 2 (HER-2) oncoprotein overamplification are associated with aggressive clinical behavior. Given the limited availability of information for Puerto Rico, we aimed to evaluate the prevalence and clinical correlates of HER-2 gene overexpression among a hospital-based female population of breast cancer cases. We analyzed data from 1,049 female patients with invasive breast cancer (diagnosed 2000-2005) at the I. González Martínez Oncologic Hospital and the Auxilio Mutuo Hospital. HER-2 status and other clinical characteristics were retrieved from the hospitals’ cancer registries, from the Puerto Rico Central Cancer Registry, and from a review of medical and pathological records. Prevalence odds ratios were estimated with 95% confidence intervals, using logistic regression models to quantify the association between HER-2 status and different clinicophatological factors. The overall prevalence of positive HER-2 expression was 22.5%. In the multivariate logistic regression model, factors significantly associated with HER-2 positivity included a diagnosis age of < 50 years, having a tumor with negative progesterone receptor (PR) status, and having regional disease (p < 0.05). No significant differences in HER-2 positivity were observed by tumor histology or estrogen receptor (ER) status (p > 0.05). This is the most comprehensive epidemiological study to date on HER-2 status in Puerto Rico. The prevalence and correlates of HER-2 overexpression in this study are comparable to those observed in US populations. Study results will aid in the development of breast cancer control strategies in Puerto Rico.